Recent Insights into Viridans streptococci Species Causing Infective Endocarditis - S. S. Jaya Lakshmi; K. V. Leela (Research Perspectives of Microbiology and Biotechnology Vol. 5, 2024)
This book chapter presents a comprehensive update on the diverse species of Viridans Streptococci implicated in the pathogenesis of infective endocarditis (IE). It explores recent insights into the epidemiology, pathogenic mechanisms, clinical manifestations, diagnostic approaches, and therapeutic considerations specific to Viridans streptococci-associated IE. The chapter highlights advancements in understanding the genetic variability, antimicrobial resistance profiles, and virulence determinants of these bacterial species, underscoring their clinical significance and implications for patient management. Additionally, emerging trends and challenges in the diagnosis and treatment of IE caused by Viridans streptococci are discussed, offering valuable perspectives for future research and clinical practice [1].